The Implementation of Narrative Content Marketing Comminications Strategy for Community Based E-commerce Products - Moses Frans Romual Silitonga; Hifni Alifahmi (Jurnal InterAct, 2017)
This research focuses on an analysis of Japanese Station and Simamaung’s e-commerce narrative content marketing communications strategy implementation for consumers who are part of a community, by using Ooden’s concept of content marketing strategy and narrative theory as the research guidance. Although this study relates to narrative, this research was not based on the paradigm of narrative or in other words the construction of the story, but rather the analysis of narrative content marketing communications strategy. This is a qualitative study based on post-positivism paradigm and  using two case studies to provide a comprehensive point of view. This study shows that a narrative content marketing communication strategy exists that may be applied through digital media to market community based e-commerce products. The strategy covers related narrative contents publication based on the interest and attraction of the target community that is able to manage and maintain the existence of the target community. Through the application of the said strategy, the owners may drive the community to make e-commerce purchases, while still being influenced by other factors related to their e-commerce businesses model.